2019
DOI: 10.1101/624676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Staphylococcus aureususes the bacilliredoxin (BrxAB)/ bacillithiol disulfide reductase (YpdA) redox pathway to defend against oxidative stress under infections

Abstract: Staphylococcus aureus is a major human pathogen and has to cope with reactive oxygen and chlorine species (ROS, RCS) during infections. The low molecular weight thiol bacillithiol (BSH) is an important defense mechanism of S. aureus for detoxification of ROS and HOCl stress to maintain the reduced state of the cytoplasm. Under HOCl stress, BSH forms mixed disulfides with proteins, termed as S-bacillithiolations, which are reduced by bacilliredoxins (BrxA and BrxB). The NADPH-dependent flavin disulfide reductas… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Thus, the S. aureus strain SH1000 of the NCTC8325-4 lineage was impaired in survival in infection assays compared to the SH1000 bshC repaired strain (Pöther et al 2013). Interestingly, the S. aureus bshA, ypdA and brxAB mutants showed similar defects in survival inside J774.1 macrophages and neutrophils, indicating that the Brx/BSH/YpdA/NADPH system is essential under infections to regenerate BSH and protein thiols (Linzner et al 2019;Mikheyeva et al 2019;Pöther et al 2013;Posada et al 2014). Future studies should investigate the physiological role of BSH and the Brx/BSH/YpdA/NADPH redox pathway in S. aureus in murine infection models with defects in the NADPH oxidase and myeloperoxidase to elucidate if BSH homeostasis provides protection against the oxidative burst of neutrophils and macrophages.…”
Section: Functions Of Bacillithiol In Detoxification and Antibiotics mentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, the S. aureus strain SH1000 of the NCTC8325-4 lineage was impaired in survival in infection assays compared to the SH1000 bshC repaired strain (Pöther et al 2013). Interestingly, the S. aureus bshA, ypdA and brxAB mutants showed similar defects in survival inside J774.1 macrophages and neutrophils, indicating that the Brx/BSH/YpdA/NADPH system is essential under infections to regenerate BSH and protein thiols (Linzner et al 2019;Mikheyeva et al 2019;Pöther et al 2013;Posada et al 2014). Future studies should investigate the physiological role of BSH and the Brx/BSH/YpdA/NADPH redox pathway in S. aureus in murine infection models with defects in the NADPH oxidase and myeloperoxidase to elucidate if BSH homeostasis provides protection against the oxidative burst of neutrophils and macrophages.…”
Section: Functions Of Bacillithiol In Detoxification and Antibiotics mentioning
confidence: 97%
“…The reduced state of BSH is maintained by the NADPH-dependent flavin disulfide reductase YpdA in S. aureus, which functions as a BSSB reductase ( Figure 3) (Linzner et al 2019;Mikheyeva et al 2019). YpdA acts in the Brx/BSH/YpdA/NADPH redox pathway to regenerate Sbacillithiolated proteins under oxidative stress in S. aureus as outlined in the next sections (Linzner et al 2019).…”
Section: Functions Of Bacillithiol In Detoxification and Antibiotics mentioning
confidence: 99%
“…It is made available under a preprint (which was not certified by peer review) is the author/funder, who has granted bioRxiv a license to display the preprint in The copyright holder for this this version posted December 2, 2020. ; https://doi.org/10.1101/2020.12.02.408641 doi: bioRxiv preprint 4 Alternatively, BSH can react directly with ROS, again leading to oxidation of BSH to BSSB 19 (Scheme 1). While GSSG is recycled by GR, a recent study showed that the flavoenzyme YpdA from Sa consumes NADPH 20 , and another confirmed that Sa YpdA reduces BSSB under aerobic conditions 21 . Evidence that BSSB is recycled by the FAD-containing NADPH-dependent disulfide oxidoreductase YpdA, which along with BrxA/B and BSH biosynthesis enzymes BshA/B/C is only present in BSH-containing bacteria, has provided insight into the understanding of the Brx/BSH/YpdA pathway and the recycling of BSSB to maintain the reduced BSH pool (Scheme 1B).…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, it was recently suggested that YpdA acts on BSSB through a conserved residue (Cys14). This was based on the ceased enzymatic activity in a YpdA C14A mutant, implying that Cys14 acts as an active site residue in YpdA for BSSB reduction 21 . The YpdA crystal structures presented in this work reveal, however, that Cys14 is located in a buried environment, ~8 Å away from the FAD isoalloxazine ring, making reactions with both FAD and BSSB unlikely ( Figures 3A and S7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation